“Proyecto De Factibilidad Para La Implementación De Un Centro De Atención Al Adulto Mayor, Para El Cantón Loja - Herrera Rodríguez, María Esperanza (2016)
In the canton Loja centers of recreation private geriatrics don't exist, where people of means and high revenues can share recreation moments and esparcimiento next to people of their age. This is our competitive advantage, the being precursors in the implementation from a Center of Attention to the biggest Adult "to REBORN" Co. Ltda. , for the canton Loja, with the purpose of offering to the biggest adults: peace, tranquility, care and a space to amuse, to train and to be in permanent activity with personal highly qualified. In the same way the realization of this project will help many people to be carried out professionally since a place it will exist where they will be able to leave daily to pleasure and with total trust to the relative that has to its care, the objective of this study is therefore, to try to improve the well-being and quality of life of the sector geriatric. To develop the present investigation project we use different methods and technical of gathering of information that served us for the elaboration of our study. Among the applied methods we have the deductive, inductive, historical method, and the statistical method who you/they guided us to follow a logical process in our study. As well as we apply different techniques to gather information, as the direct observation, the interview applied the directors of the centers that offer attention to the biggest adult and the surveys applied to a sample of 382 families of the canton Loja like possible clients. In what concerns to the market study it was determined the offer and the demand, as well as the existent unsatisfied demand and the factors that impact in the service to offer such as: Service, Price, Square, Promotion and Publicity. In the made Technical Study we determine the size that corresponds to the installed capacity and used, and the localization of the project where we determine the macro and microlocalización, attaching the outline of the location of the center that will be in the parish the Valley in the Neighborhood Sallows North, urban perimeter of the canton Loja whose space physique has all the basic services for its normal operation, since according to data of the survey applied to the families Lojanas they would like that the center is implemented in the urban area, in what concerns to the engineering of the project it is exposed the component and technological tools to offer the service of attention and care to the biggest adults, the physical distribution of the center, the process of the service in all its phases as well as it was considered the environmental aspect. As for the organizational and administrative study he/she intends the legal organization the center like a Company of Limited Responsibility that he/she will have three partners settling down whose name or social reason is "to REBORN" Co. Ltda., as for the administrative study he/she thinks about the organizational structure through the flowcharts and the manual of functions. In the Financial Study it is shown that for the creation of the Center of Attention to the biggest Adult "to REBORN" Co. Ltda., an investment is required of $146.863,98 dollars. The partners founders will contribute a total value of $73.431,99 dollars that represents 50% of the investment and the difference with a credit for the quantity of $73.431,99 that represents 50% of the investment. The State of Losses and Earnings show a net utility of $15.348,64 and so forth in the first period he/she will go increasing he/she stops the following years. In the evaluation of the project it was evidenced that the net current value is positive with a value of $47.279,63; the internal rate of return is of 19,70% it is bigger than the cost of opportunity of the capital of 10%; the relationship benefits cost it indicates that for each invested dollar it will be obtained 0,48 cents of yield; the investment will recover in 4 years, 3 months and 10 days; and based on the analysis of the sensibility a satisfactory result is demonstrated that allows 7,28 increment% in the costs and a decrease in the revenues of 4,98% respectively, the project is not that is to say sensitive to these changes. As for the conclusions it is considered feasible the implementation of the Center of Attention to the biggest Adult, since when identifying the objective market the interest of the relatives of the adults it was observed bigger than the canton Loja to make use of our service, for what you leave here in definitive reflected the final balance of this investigation work that represents in form logic, white and concise the obtained results, based on a good study that precedes the project in yes. The recommendations were elaborated leaning on in the conclusions that seek to be the reflection of future actions. It is necessary to highlight that this project will constitute a practical guide of consultation for the students of the National University of Loja in the event of undertaking a similar company to ours.